The Effect of Islamic Spiritual Mindfulness on Self-Efficacy in Anger Management among Schizophrenic Patients - Dwidiyanti, Meidiana; Rahmawati, Ashri Maulida; Sawitri, Dian Ratna (Department of Nursing, Faculty of Medicine, Diponegoro University, 2021)
Background: The prevalence of schizophrenia has increased in the last few years. Nevertheless, methods in assisting schizophrenic patients have not improved significantly. Islamic spiritual mindfulness is a spiritual approach that can help schizophrenic patients increase their self-efficacy in anger management. However, the application of this intervention is still not well researched.Purpose: This study aimed to determine the effect of Islamic spiritual mindfulness on self-efficacy in anger management among schizophrenic patients.Methods: This study utilized a pre-post quasi-experimental design with a control group. A total of 54 schizophrenic patients were purposively recruited and divided into two groups: the intervention group (n=27) and the control group (n=27). The intervention group received four sessions of Islamic spiritual mindfulness in two weeks, while the control group received a standard intervention from the hospital. The data were collected using the Regulatory Emotional Self-Efficacy (RESE) scale and analyzed using the t-test.Results: The results showed a significant difference in self-efficacy scores between the control and intervention groups (p=0.000) after the intervention. In the pre-test, the mean score of self-efficacy in the intervention group was lower than the control group (M=28.15 vs. M=30.26) without a significant difference. However, in the post-test, a significant difference in self-efficacy between the intervention and control groups was found (M=46.44 vs. M=46.44; p=0.000).Conclusion: Islamic spiritual mindfulness significantly affects self-efficacy among schizophrenic patients. The Islamic spiritual mindfulness can be applied as a new form of approach to increase self-efficacy in schizophrenic patients.